In-Person Healthcare Simulation: An Umbrella Review of the Literature - Palaganas, Janice C; Mosher, Cynthia; Wawersik, Dawn; Eller, Susan; Kirkpatrick, Amanda J; Lazarovici, Marc; Brown, Kristen M; Stapleton, Stephanie; Hughes, Patrick G; Tarbet, Amanda; Morton, Alex; Duff, Jonathan P; et al. (Simulation in healthcare : journal of the Society for Medical Simulation, 2025)
Given the large accumulation of research focused on the effectiveness of in-person simulation-based education (SBE), this umbrella review-or systematic review of systematic reviews-was conducted using Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines to analyze collective findings and close identified literature gaps. This study presents a descriptive analysis of the most effective modalities, methods, and measurements of in-person SBE, as well as major themes that emerged during analysis as it relates to SBE outcomes.The major patterns or themes that emerged confirm for the first time a longstanding sentiment in the literature, specifically the following: a need to produce higher-quality research with greater rigor, larger sample sizes, more randomized controlled trials, mixed methods, and longitudinal studies. These findings suggest a need to redirect scientific efforts in SBE. Despite the nearly ubiquitous issues noted across the systematic reviews' findings, results of this umbrella review seem to support the notion that in-person simulation-based education improves learning outcomes including technical and nontechnical skills and behavioral and attitudinal change. Analyses highlighted the need to improve overall research approaches and reduce redundancy, as well as the need to standardize terminology, broaden global diversity, and push for further research funding opportunities to support these efforts.